Efficiency of trifloxystrobin and tebuconazole, in a commercial formulation, associated with protective fungicides to control alternaria brown spot on ‘murcott’ tangors - Nouhra, Guilherme [UNESP]; Poloni, Nadia Maria [UNESP]; Pereira, Fernanda Dias [UNESP]; De Goes, Antonio [UNESP] (FapUNIFESP (SciELO), 2021)
Among fungal diseases, Alternaria brown spot (ABS) is the most important disease for “Murcott” tangors, causing leaf drop, spots, fruit drop and consequently heavy losses. The present study evaluated the efficiency of two levels of trifloxystrobin and tebuconazole, in commercial formulation, combined with pyrimethanil or water-soluble copper, in comparison with copper oxychloride, on ABS control in a 15-year-cultivation “Murcott” tangor orchard in Estiva Gerbi, Sao Paulo State, Brazil. Treatments were composed of the tank mixture of trifloxystrobin and tebuconazole at 0.80 L ha-1 with the following fungicides (L or kg commercial product 2000 L-1): T1-pyrimethanil (1.0); T2-pyrimethanil (2.0); T3-soluble copper sulfur (1.0); T4-copper oxychloride (3.60). Split-block design was adopted, in subplots, with three replicates containing ten plants on the row between two adjacent rows. Fungicides were applied with an FM Copling turbo sprayer, at a flow of 100 mL (m3)-1. In total 17 fungicide applications were performed at intervals varying between 12 and 15 days. Evaluations consisted of determining the severity levels of symptoms on fruits in three periods (S1, S2 and S3) and the number of injuries on fruits at harvest. Treatments combining trifloxystrobin and tebuconazole with pyrimethanil, in two levels, were efficient in controlling the pathogen, similarly to the results of the standard treatment, represented by the combination of trifloxystrobin and tebuconazole with copper oxychloride.
Eficiência de trifloxistrobina e tebuconazole, em formulação comercial, associados a fungicidas protetores no controle da mancha marrom de Alternária em tangor ‘‘Murcott”
Keywords: Alternaria alternata; Chemical control; Citrus reticulata